The distribution of araceae in riverrine areas of Bukit Bakar, Machang, Kelantan, Peninsular Malaysia - Norazrena Mohmad Jan (2015)
The study was conducted to identify the species of Araceae in riverine areas, the abundance, and diversity and ecology of Araceae in riverine areas. This study used systematic sampling method. Identification of species is based on morphological characteristics. The application of Geographic Information System (GIS). Shannon - Wienner Diversity Index and Margalef Index was used to map the diversity and distribution of Araceae. Microsoft Excel was also used to calculate the abundance of Araceae. A total of eleven species from seven genus of Araceae were identified at Bukit Bakar. Colocasia esculenta is the most abundant species due to adaptation to grow in open and disturbed areas. Alocasia puber and Homalomena wallichii are the least species found in the area. Others species are Aglaonema simplex, Homalomena griffithii, Homalomena humillis, Lasia spinosa, Rhaphidophora beccarii, Rhaphidophora falcata, Schismatoglottis calyptrata and Schismatoglottis wallichii. Araceae species mostly found at the moist and at the river banks. The Shannon-Wienner Diversity Index is 1.4115 while the Margalef index is 0.0163.